ORTONORMALISASI VEKTOR BASIS DENGAN PROSES GRAM SCHMIDT - Irma Budi Wardani; Hartanto Sunardi (Universitas PGRI Adi Buana Surabaya, 2015)
Gram schmidt process is one of linear algebra roles that associated by basis vector. This thesis aims to determine theoretically step by step in the process of gram schmidt. Gram schmidt process is a method that used to convert an arbitrary basis vector into an orthogonal basis vector. After orthogonal basis vector had been obtained, the orthogonal basis vector was compiled into an orthonormal basis through step by step. A vector on will be expressed as a basis vector if the vector if the vectors in are linear independently and spinning against . And a basis vector can be expressed as a set of orthonormal vectors, then the vector is an orthogonalvector and has norm = 1. If the basis vector has norm 1, to normalize the basis vector by using gram schmidt process. Keywords: vector base, ortonormalisasi, gram schmidt proses.